Ocular Convergence Deficits in Schizophrenia - Bolding, Mark S. (Frontiers Media S.A., 2012)
Individuals with schizophrenia (SZ) have been reported to exhibit a higher prevalence of convergence insufficiency (CI) than the “normal” adult population. The purpose of this study was to determine if individuals with SZ exhibit clinical signs of CI and to determine if the Convergence Insufficiency Symptom Survey (CISS) is an effective instrument for identifying CI in this population. Twenty participants with SZ and 20 healthy controls (HC) completed the study. The prevalence of CI (15%) in the SZ group was slightly higher than reported norms, but the difference was not significant. The SZ group had significantly higher scores on the CISS than the HC group, but the CISS scores did not correlate with clinical measures of CI in individuals with SZ. The only exception was that SZ patients had a significantly reduced fusional reserve as determined by Sheard’s criteria. Further study is needed to determine why individuals with SZ reported symptoms associated with CI even though clinical measures did not support this diagnosis.